2021
DOI: 10.7554/elife.59384
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma TgATG9 is critical for autophagy and long-term persistence in tissue cysts

Abstract: Many of the world’s warm-blooded species are chronically infected with Toxoplasma gondii tissue cysts, including an estimated one-third of the global human population. The cellular processes that permit long-term persistence within the cyst are largely unknown for T. gondii and related coccidian parasites that impact human and animal health. Herein, we show that genetic ablation of TgATG9 substantially reduces canonical autophagy and compromises bradyzoite viability. Transmission electron microscopy revealed n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 79 publications
5
28
0
Order By: Relevance
“…This was corroborated in a following study from Smith et al [130] that demonstrated that autophagy is constitutively induced in bradyzoites and essential for cyst survival. Inhibition of this process through TgAtg9 gene deletion resulted in bradyzoite death and a dramatic decrease in the brain cyst burden in challenged mice, mirroring the results obtained for the TgCPL knockout strain [128,130]. It still remains to be determined whether autophagy and VAC digestion following encystation are required to renew organelles during the chronic stage (and thus is critical for cellular homeostasis), or if it reflects a starvation response to provide essential substrates to sustain the bradyzoite.…”
Section: Amino Acid Transporterssupporting
confidence: 57%
See 1 more Smart Citation
“…This was corroborated in a following study from Smith et al [130] that demonstrated that autophagy is constitutively induced in bradyzoites and essential for cyst survival. Inhibition of this process through TgAtg9 gene deletion resulted in bradyzoite death and a dramatic decrease in the brain cyst burden in challenged mice, mirroring the results obtained for the TgCPL knockout strain [128,130]. It still remains to be determined whether autophagy and VAC digestion following encystation are required to renew organelles during the chronic stage (and thus is critical for cellular homeostasis), or if it reflects a starvation response to provide essential substrates to sustain the bradyzoite.…”
Section: Amino Acid Transporterssupporting
confidence: 57%
“…CPL-deficient bradyzoites were also shown to accumulate autophagosomes, indicating autophagy could be essential to chronic persistence [128]. This was corroborated in a following study from Smith et al [130] that demonstrated that autophagy is constitutively induced in bradyzoites and essential for cyst survival. Inhibition of this process through TgAtg9 gene deletion resulted in bradyzoite death and a dramatic decrease in the brain cyst burden in challenged mice, mirroring the results obtained for the TgCPL knockout strain [128,130].…”
Section: Amino Acid Transportersmentioning
confidence: 54%
“…These findings indicate that apicomplexan Atg8 homologs seem to be clearly different from yeast and mammalian Atg8s, which are not strictly necessary for cell growth under nutrient-rich conditions ( 45 , 46 ). However, a recent work has shown that, in Toxoplasma bradyzoites,TgAtg8 also benefits bradyzoite viability due to its abilities of efficient autophagosome formation and transportation of autophagic materials to VAC ( 16 ). Therefore, the dual functions of TgAtg8, apicoplast biogenesis in tachyzoites and viability in bradyzoites, suggest that it may be leveraged for the development of drugs against both acute and chronic Toxoplasma infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that autophagosome-like structures can be observed in response to nutrient starvation and endoplasmic reticulum stress in tachyzoites ( 14 , 15 ) and bradyzoites ( 16 , 17 ) of Toxoplasma . However, besides its cytosolic and autophagosomal localizations, the Toxoplasma gondii Atg8 (TgAtg8) homologue also localizes to the outermost membrane of the apicoplast, a nonphotosynthetic plastid-like organelle shared by most members of Apicomplexa ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the chronic stage parasites (bradyzoites), cathepsin L-depleted cells accumulate TgATG8-positive puncta, suggesting an arrest of autophagy [103]. The recycling of amino acids by autophagy may be crucial for the persistence of Toxoplasma in its host, as demonstrated by specific inactivation of ATG9 in this stage [104]. While Apicomplexa of the coccidia subclass (including Toxoplasma) possess an ATG9 homolog that seems essential for canonical autophagy akin to other eukaryotic models, other Apicomplexa like Plasmodium do not, which raises the question of how autophagosomes can be generated in these parasites.…”
Section: Autophagosome-like Vesicles In Apicomplexamentioning
confidence: 99%